Congenital Pseudoarthrosis Tibia (CPT) performed Free Vascularized Fibular graft : A case report - Muhammad Bayu Wicaksono (Journal of Global Pharma Technology, 2019)
AbstractCongenital pseudarthrosis of the tibia (CPT) remains one of the most challenging problems confronting the orthopaedic surgeon. The operative results are frequently less than successful; many cases require several surgical procedures, and a significant number of them ending in amputation. The purpose of this study was to access the surgical results, complications, secondary procedures, and long-term results of free vascularized fibular graft (FVFG). We reported a case of a 5 years old boy complained unable to walk, was diagnosed as Congenital Pseudarthrosis of the left tibia. The patient had been doing several operation procedure, finally performed FVFG. After 5 months follow up, ORIF with intramedullary Kirschner wire provided stability, and acceptable alignment resulted in bony union. However, even achieving union of pseudarthrosis is not enough for the resolution of the disease. This is only half of the problem, the other half is to maintain union. Keywords : Congenital pseudoarthrosis tibia, Free Vascularized Fibular graft